Needs Analysis for Development of Learning Multimedia to Facilitate Introduction of English in Early Childhood - Indrawati Indrawati; Sigit Purnama (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2024)
This study aims to analyze the needs of developing multimedia English learning for early childhood, focusing on supporting children's engagement and understanding. Through surveys and interviews with early childhood teachers. This research identified five main needs: (1) Learning Materials that include basic vocabulary and simple expressions in relevant themes; (2) Visual and Audio Design that is attractive and child-friendly; (3) Interactivity, such as quiz and game features to increase engagement; (4) Flexibility of Use that allows the multimedia to be accessed both at home and school; and (5) Leveled Materials according to children's cognitive development. The results show that interactive and flexible multimedia can increase children's motivation and participation in learning English. In addition, the flexibility of using multimedia also facilitates parental involvement, supporting more sustainable learning. This research supports the theories of constructivism and technology-based learning in early childhood education, and provides practical contributions for developers and educators. The findings' recommendations are expected to guide effective multimedia design for early childhood English language introduction.